Frequency of Aplastic Anemia Among Adults Patient with Pancytopenia: A Cross-Sectional Study Design - Farhan Zeb, Saqib Pervez, Asif Khan, Mudassar Bilal, Bushra Khan, Amarjeena Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency aplastic anemia among adult patients with pancytopenia. Place and duration of study:The study is conducted at Department of Medicine, MTI-Lady Reading Hospital, Peshawar and the duration of study is From 25-04-2018 to 25-10-2018. Material and Method: It is a Descriptive cross sectional study design having sample size of 135 patients, this study using 95% confidence level and 7% margin of error, under WHO software for sample size determination. The sampling technique we have used in this study is the non-probability consecutive sampling. All adult patients with newly diagnosed pancytopenia of any duration, Age group above 18 years to 60 years belongs to any gender are included in this study design. SPSS 23 was used to evaluate all the data.Mean and Standard Deviation was calculated frequency and percentages were calculated. Using the chi square test results are examine the effect modification. A p-value of 0.05 or below was considered significant. Results: At the MTI-Lady Reading Hospital in Peshawar's Department of General Medicine, 135 patients participated in this study. According to descriptive data, the mean and SDs for age were recorded as 55+12.85 and 3+1.18, respectively. In the 18–30 age range, there were 27 (20%) patients, whereas the 31–60 age group had 108 (80%) individuals. In a similar manner, 44 (32.59%) patients were recorded as female and 91 (67.40%) patients were recorded as male. According to frequency and prevalence rate for aplastic anaemia, 103 (76.29%) patients were identified as having this condition. Practical Implications: The current study's objective is to determine the prevalence of aplastic anaemia in people with adult pancytopenia. Despite the availability of study, statistics show that the severity of aplastic anaemia varies from population to population, and pancytopenia is not uncommon in our society. Conclusion: This study evaluated that aplastic anaemia is the most prevalent cause of pancytopenia in the Khyber Pukhtunkhwa population, and that bone marrow aspiration is a recognised diagnostic method for the assessment of pancytopenia. Keywords: Aplastic anemia, Bone marrow, Megaloblastic Anemia, Pancytopenia, Bone marrow failure Syndrome, . Myelophthisic anemia, Thrombocytopenia.